The Role of Tissue-Resident Macrophages in the Development and Treatment of Inflammatory Bowel Disease - Ma, Shengjie; Zhang, Jiaxin; Liu, Heshi; Li, Shuang; Wang, Quan (Frontiers in Cell and Developmental Biology, 2022)
Inflammatory bowel disease (IBD), comprising Crohn’s disease and ulcerative colitis, is a refractory disease with many immune abnormalities and pathologies in the gastrointestinal tract. Because macrophages can distinguish innocuous antigens from potential pathogens to maintain mucosa barrier functions, they are essential cells in the intestinal immune system. With numerous numbers in the intestinal tract, tissue-resident macrophages have a signiﬁcant effect on the constant regeneration of intestinal epithelial cells and maintaining the immune homeostasis of the intestinal mucosa. They also have a significant influence on IBD through regulating pro-(M1) or anti-inﬂammatory (M2) phenotype polarization according to different environmental cues. The disequilibrium of the phenotypes and functions of macrophages, disturbed by intracellular or extracellular stimuli, influences the progression of disease. Further investigation of macrophages’ role in the progression of IBD will facilitate deciphering the pathogenesis of disease and exploring novel targets to develop novel medications. In this review, we shed light on the origin and maintenance of intestinal macrophages, as well as the role of macrophages in the occurrence and development of IBD. In addition, we discuss the molecular and cellular mechanisms participating in the polarization and functions of gut macrophages, the potential treatment targets, applicable drugs, and current clinical trials for IBD.